Road Pavement Damage Assessment Using the Bina Marga Method and GIS on Gayam – Sidorejo Road - Dimas Bagus Prasetyo; Hendrata Wibisana; Aulia Dewi Fatikasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Road pavement deterioration is a common problem in transportation infrastructure that can reduce road safety, comfort, and traffic efficiency. The Gayam–Sidorejo road section in Kediri District serves as an important interregional connector with relatively high traffic volume, which can accelerate pavement deterioration; therefore, an evaluation of pavement conditions is required to determine appropriate maintenance strategies. This study aims to analyse pavement damage on the Gayam–Sidorejo road section using the Bina Marga method and to visualise its spatial distribution through GIS-based mapping to support more effective road maintenance planning. The research was conducted on an 8.383 km road section divided into nine observation segments, with data collected through field surveys including road inventory, pavement damage identification, and traffic volume surveys. The collected data were analysed using the Bina Marga method to determine road condition values and maintenance priorities, and spatial visualisation was performed in ArcGIS. The results show that the Average Daily Traffic (ADT) is 10,808 pcu/day, which falls into traffic class 6. The identified pavement damage types include edge cracking, transverse cracking, longitudinal cracking, alligator cracking, rutting, potholes, and patching. The analysis further indicates that Segment 6 has the worst pavement condition, with a total damage area of 899,60 m² and a damage percentage of 21,94%, indicating significantly higher deterioration than in other segments. Overall, most road segments have priority values between 5 and 6, indicating that they require periodic maintenance. Integrating the Bina Marga method with GIS mapping provides clearer spatial information on pavement conditions and supports more effective, targeted road maintenance planning. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and Communities